THE DEVELOPMENT OF PROGRAMME MODELS BASED ON PLYOMETRIC EXERCISES COMBINED WITH TECHNICAL PROCEDURES DESIGNED TO OPTIMIZE SPECIFIC PHYSICAL TRAINING IN JUNIOR HANDBALL PLAYERS (15-16 YEARS) - Stoian Iulian (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2014)
The present study aims to verify the plyometric training method associated with technical processes from the game of handball, experiment driven by the need of adapting the learning process in accordance with the baggage of knowledge and expressing possibilities of young handball players. We started from the assumption that the combination of plyometric contraction regimes with basic technical processes can contribute to increasing the general and specific motive capacity, and to constantly improving the training of handball players. The research was conducted by analyzingexisting conceptsaboutplyometricexercises, adapting them tohandball's practiceandimplementing the conclusions in specific training. The results revealedthe possibility ofconceptionsome training programsbased onplyometricmethod. Checkingtheirpracticeled to anupward trend in match results, fact which suggests that a properly designed program can be an important support in training handball players for specific competitive effort.